2000
DOI: 10.1002/clc.4960231015
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between mean right atrial pressure and doppler parameters in patients with right ventricular infarction

Abstract: SummaryBackground: The incidence of an inferior left ventricular infarction involving the right ventricle is very high, ranging from 14 to 84%. Isolated right ventricular infarction accounts for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Interestingly, in the present study, no independent association between significant renal impairment and estimated RA pressure was observed, suggesting that the association with RV dysfunction may not be mediated by increased central venous pressure. However, the estimation of right atrial pressure on echocardiography through the evaluation of the inferior vena cava diameter and collapsibility may correlate less closely with invasively derived right atrial pressure in patients with significant TR [ 26 ]. Furthermore, estimated RA pressure may change acutely with alterations in volume or clinical status, whereas RV dysfunction may more accurately identify patients who are exposed to the cumulative effects of chronically elevated central venous pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in the present study, no independent association between significant renal impairment and estimated RA pressure was observed, suggesting that the association with RV dysfunction may not be mediated by increased central venous pressure. However, the estimation of right atrial pressure on echocardiography through the evaluation of the inferior vena cava diameter and collapsibility may correlate less closely with invasively derived right atrial pressure in patients with significant TR [ 26 ]. Furthermore, estimated RA pressure may change acutely with alterations in volume or clinical status, whereas RV dysfunction may more accurately identify patients who are exposed to the cumulative effects of chronically elevated central venous pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiography remains the main technique in assessing right ventricular function in children with CHD 2 . Systolic and diastolic right ventricular echocardiographic values have been validated against cardiac catheterisation data in the adult population, 4 8 but minimal data exist in the paediatric congenital heart population correlating echocardiographic variables of right ventricular function with cardiac catheterisation data. Even less data exist validating the newer echocardiographic techniques of tissue Doppler imaging and deformation analysis for assessing right ventricular function in the paediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…Adult studies have shown relationships between various echocardiographic systolic and diastolic values with invasive haemodynamic measurements 4 5 In addition, the newer echocardiographic techniques of tissue Doppler imaging and deformation analysis have also been shown to correlate with catheterisation values of systolic and diastolic function in adult studies; 6 – 8 however, minimal data exist in children documenting correlations between catheterisation values of function with echocardiographic measurements of function 9 …”
mentioning
confidence: 99%
“…To assess this using POCUS, the hepatic veins represent a window of this physiologic principle. The identification of a dominant diastolic component can reliably identify elevated RAP (50 52), whereas a retrograde systolic component is suggestive of, but not synonymous with, hemodynamically significant tricuspid regurgitation (53,54). Although the reproducibility of the assessment has been reported to be excellent (55), the use of concurrent electrocardiogram tracing to ensure the proper identification of the systolic and diastolic phases remains critical for accurate interpretation.…”
Section: Role Of Pocusmentioning
confidence: 99%